Recent advances in photo‐ or electro‐chromic smart windows and their thermal regulation - Zhen Du; Shuo Wang; Chang Gu; Guojian Yang (Responsive Materials)
Abstract Windows are considered to be a major contributor to energy consumption in buildings. Smart windows, as a replacement for traditional windows, can reversibly regulate the transmittance of sunlight, enabling indoor thermal regulation and promising to reduce building energy consumption, thus attracting increasing attention. Especially, the smart windows based on photochromic (PC) or electrochromic (EC) materials have been widely researched due to zero energy input and potential for seasonal adaptability of PC smart windows, as well as the unique active adjustment mode of EC smart windows. These smart windows hold promising application prospects in the field of thermal regulation of future low energy‐consumption buildings. However, issues such as the difficulty in scaling up EC smart windows, the slow response time of PC smart windows, and the poor cycling stability and durability common to both EC and PC smart windows limit their development in the field of building thermal regulation. Focusing on the important progresses and challenges of these smart windows based on PC or EC materials, we systematically review the typical researches reported in recent years. This review covers the evaluation parameters of thermal regulation performance, innovative mechanisms, optical regulation optimization methods, and developing status of the smart windows based on PC or EC materials. Moreover, we also discuss the existing issues with the current smart windows and propose targeted improving suggestions. Hopefully, this review can promote the further development of the smart thermal regulation technologies with PC or EC windows.